MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN ALAT PERAGA - Pardossi, Augus (Jurnal Pendidikan Matematika dan IPA, 2018)
AbstractÂ The props are a tool or a complement that the facilitator (teacher) uses to interact with the students. This study aims to know and analyze the increase in activity and learning outcomes of students of class VIII A SMP Negeri 20 Pontianak after learning by using props. This research is a classroom action research consisting of 3 cycles. Each cycle consists of planning, action, observation and reflection. Based on the result of data analysis from the preliminary test results obtained 3 students who are tuntasa (8.33%) and not complete 33 students (91.67%), while the initial activity of students is categorized active 12 Students (33.3%) and inactive 24 students (66.7%). In the first cycle, the average score of 62.97 with the complete category of 17 students (47%) and the unfinished categorization of 19 students (53%) and the active student activity were 26 students (72.2%) and the inactive 10 students (27 , 8%). Cycle II average score 64,53 with complete category of 20 students (55,6%) and categorize is not complete 16 students (44,4%) and active student activity is 32 student (88,89%) and who is not active 4 students (11.11%). While in cycle III the average score 82,28 with complete category 31 students (86,11%) and categorize is not complete 5 student (13,89%) with activity level of student active 100%. Increasing activity and result learn that happened Indicates that the teaching aids learning tools implemented according to the expected learning objectives.Keywords: props, activities, learning outcomes